Value assesment of the Chilean built heritage trough sustainability and implementation of management models - Razote Urioste, Romina (2015)
This article analyzes the programs adopted by the Chilean Government for the value assessment of its built heritage. Value assessment is a recognition of the present values in these monuments. This recognition is effective only when it carries the necessary measures for the conservation, recovery and evaluation of the edification. In that sense, the concept of sustainability concept is indispensable for understanding heritage management in the long-term. Considering this, in the article the criteria that has been used for the development of the value assessment program of Chilean heritage, in particular regarding the implemented management models, are described, for these are the instruments that make possible the sustainability and conservation of the built heritage long term in the long term.